Acute effects of full lower limb compression garment (CG) on the lower limb skeletal muscle performance recovery following downhill running in recreational athletes - Low, Jaclyn Ai Mei (Nanyang Technological University, 2022)
Compression garments (CG) are increasingly being used in sporting disciplines for its purported benefits in improving post-exercise recovery and exercise performance. As a relatively inexpensive and safe-to-use modality, more studies are being conducted on the research of its mechanisms and efficacy which often resulted in inconclusive results due to its heterogeneity. Therefore, the purpose of this study was to determine the effectiveness of CG on skeletal muscle performance recovery via assessment of physiological responses (CK concentrations), performance efficacy (Beep Test results) and perceptions of muscle soreness (PMS). Using a randomized crossover design, 11 males and 5 females (age 23.63 ± 1.41) visited on six separate sessions to carry out the DHR protocol on the third and fifth session upon completion of screening. Participants were given the CG post-DHR for wear during a 24-hour recovery period till the following session and crossover when completed. Blood samples to determine serum CK concentration was collected, and Beep Test results were recorded prior to a 72-hour washout period. A Friedman’s test revealed no statistical significance between CK concentrations with or without the use of CG during the recovery period (p > 0.05). However, ANOVA analysis of Beep Test showed a significant effect indicating improvement in performance efficacy (p < 0.05). PMS was also reduced by 18.13 points with use of CG. Overall, the use of CG following moderate-intensity DHR showed potential in the acceleration of recovery in muscle function and perceptions of DOMS in recreational athletes but failed to elicit responses CK activity post-exercise.